The Biathlon Injury and Illness Surveillance (BIIS) project protocol: a prospective cohort study across two World Cup seasons - Fitzpatrick, J.; Panagodage Perera, N. (BMJ Open Sport & Exercise Medicine, 2020)
Reliably and accurately establishing injury and illness epidemiology in biathletes will provide insight into seasonal changes, provide potential to better embed innovative prevention strategies and advance sports medicine through the provision of effective healthcare to biathletes. The main objective of the Biathlon Injury and Illness Study (BIIS) is to provide the first comprehensive epidemiological profile of injury and illness in biathlon athletes during two consecutive Biathlon World Cup seasons over 2-years.